Highly sensitive lipid detection and localization in atherosclerotic plaque with a dual‐frequency intravascular photoacoustic/ultrasound catheter. Issue 3 (1st June 2020) - Cao, Yingchun; Alloosh, Mouhamad; Sturek, Michael; Cheng, Ji‐Xin
Abstract: Intravascular photoacoustic/ultrasound (IVPA/US) is an emerging hybrid imaging modality that provides specific lipid detection and localization, while maintaining co‐registered artery morphology, for diagnosis of vulnerable plaque in cardiovascular disease. However, current IVPA/US approaches based on a single‐element transducer exhibit compromised performance for lipid detection due to the relatively low contrast of lipid absorption and conflicting detection bands for photoacoustic and ultrasound signals. Here, we present a dual‐frequency IVPA/US catheter for highly sensitive detection and precision localization of lipids. The low‐frequency transducer provides enhanced photoacoustic sensitivity, while the high‐frequency transducer maintains state‐of‐the‐art spatial resolution for ultrasound imaging. The boosted capability of IVPA/US imaging enables a multi‐scale analysis of lipid distribution in swine with coronary atherosclerosis. The dual‐frequency IVPA/US catheter has a diameter of 1 mm and flexibility to easily adapt to current catheterization procedures and is a significant step toward clinical diagnosis of vulnerable plaque. Abstract : A dual‐frequency intravascular photoacoustic/ultrasound catheter design is developed and validated for lipid‐rich atherosclerotic plaque detection. By combining low‐frequency transducer for highly‐sensitive lipid detection and high‐frequency transducer for accurate localization in a single catheter with 1 mm diameter, this dual‐frequency catheter design largely improves the performance of intravascular photoacoustic imaging and takes a step forward for the translation of this imaging modality for diagnosis of vulnerable plaque at its early stage.